2012
DOI: 10.1007/s00253-012-4097-x
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous nutrient removal and lipid production from pretreated piggery wastewater by Chlorella vulgaris YSW-04

Abstract: The feasibility of using a microalga Chlorella vulgaris YSW-04 was investigated for removal of nutrients from piggery wastewater effluent. The consequent lipid production by the microalga was also identified and quantitatively determined. The wastewater effluent was diluted to different concentrations ranging from 20 to 80 % of the original using either synthetic media or distilled water. The dilution effect on both lipid production and nutrient removal was evaluated, and growth rate of C. vulgaris was also mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(46 citation statements)
references
References 32 publications
2
43
1
Order By: Relevance
“…26 On ACCEPTED MANUSCRIPT ACCEPTED MANUSCRIPT 7 beginning of the experiment, wastewater was filtered using 0.2µm filters (Corning® bottle-top vacuum filters) and filtrates were analysed for physic-chemical parameter. On end of the experiment (10 th ), algal biomass was harvested by centrifugation at 3000 rpm for 15 min at 4 o C as reported, 27 and remaining wastewater (supernatant) was filtered using 0.2µm filters. Then, filtrates were subjected to physico-chemical analysis.…”
Section: Nutrient Removal Analysis Of Wastewatermentioning
confidence: 99%
“…26 On ACCEPTED MANUSCRIPT ACCEPTED MANUSCRIPT 7 beginning of the experiment, wastewater was filtered using 0.2µm filters (Corning® bottle-top vacuum filters) and filtrates were analysed for physic-chemical parameter. On end of the experiment (10 th ), algal biomass was harvested by centrifugation at 3000 rpm for 15 min at 4 o C as reported, 27 and remaining wastewater (supernatant) was filtered using 0.2µm filters. Then, filtrates were subjected to physico-chemical analysis.…”
Section: Nutrient Removal Analysis Of Wastewatermentioning
confidence: 99%
“…In fact, Chlorella like species has been reported to release up to 12.5% from the total assimilated carbon as extracellular organic compounds [28]. Many flask studies without additional CO 2 feeding to boost autotrophic growth demonstrated algae-mediated COD removal from piggery wastewater [9,11,25,26]. Some studies with additional CO 2 feeding also demonstrated removal of COD [3,10,12].…”
Section: Removal and Release Of Carbon During The Microalgal Growthmentioning
confidence: 94%
“…However, the competition with the other microorganisms decreased the lipid productivity slightly in the non-sterilized wastewater compared to the sterilized wastewater. Microalgal lipid production from piggery wastewater has previously been mainly studied using sterilized wastewater [3,[9][10][11]25], although treatment of non-sterilized piggery wastewater in algal ponds has been studied without measuring the lipids [37]. For example, Whang et al [11] studied lipid production of C. pyrenoides with piggery wastewater in 1 L conical flasks.…”
Section: Composition Of Biomass and Production Of Lipidsmentioning
confidence: 98%
See 1 more Smart Citation
“…Since low phosphorous (P) and nitrogen (N) concentrations are typically the limiting factors of algal blooms in balanced aquatic environments, introducing untreated (nutrient-rich) effluents instigates their growth. Various studies have successfully demonstrated the potential of microalgae as a treatment option for effluent from livestock production (Wilkie and Mulbry 2002;Ji et al 2013) and municipal wastewater treatment plants (Åkerström et al 2014). The N and P uptake by periphytic algal communities grown in an algal turf scrubber system (ATS) was evaluated as a treatment option for a nutrient-rich creek in Northwest Arkansas (Sandefur et al 2011).…”
Section: Introductionmentioning
confidence: 99%